Biochar manure decreases ammonia volatilization loss and sustains crop productivity in rice paddy - Canatoy, Ronley C.; Cho, Song Rae; Galgo, Snowie Jane C.; Park, So Yeong; Kim, Pil Joo (Frontiers in Environmental Science, 2024)
Manure application is a recommended method to improve soil quality and mitigate global warming via soil carbon (C) sequestration. However, such application can significantly increase ammonia (NH3) volatilization loss and cause secondary environmental problems, such as acidification, eutrophication, and particulate matter formation. To investigate the potential of reducing NH3 emissions in flooded rice paddies, three types of stabilized swine manure amendments (fresh, composted, and biochar) were applied at a rate of 12 Mg ha−1 (dry weight) under standard fertilization (N–P2O5–K2O = 90–45–57 kg ha−1), and NH3 emission was characterized using the static chamber method. Regardless of manure management practices, NH3 fluxes increased significantly immediately after application of an inorganic nitrogen (N) fertilizer (urea). The manure was applied completely as the basal fertilizer before rice transplanting, but the NH3 emission rates increased more dramatically following urea application in the manure treatments. Fresh and composted manure applications significantly increased seasonal NH3 volatilization losses compared to the control but the biochar did not. Compost manure significantly increased rice grain productivity owing to the higher N content, while fresh and biochar manures did not increase rice productivity because of fewer panicles per hill and fewer grains per panicle. Consequently, biochar application resulted in lower NH3 flux intensity and seasonal NH3 flux per grain yield, whereas fresh and compost manures substantially increased this intensity. Therefore, biochar manure may be a more reasonable organic amendment than fresh and composted manures for reducing NH3 emission impacts on rice paddies.